PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING PADA KONSUMEN GALERY RJ BENGKULU - Siska Yeliza; Ade Tiara Yulinda (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of shopping lifestyle and fashion involvement on impulse buying among consumers at Galery RJ Store in Bengkulu. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 100 respondents who are active customers of the store. The data were analyzed using multiple linear regression. The results show that both shopping lifestyle and fashion involvement have a positive and significant effect on impulse buying. These findings indicate that the higher the shopping lifestyle and fashion involvement, the more likely consumers are to engage in impulse buying. This study provides important implications for fashion business actors in designing more effective marketing strategies. Keywords: Shopping Lifestyle, Fashion Involvement, Impulse Buying